2018
DOI: 10.4155/tde-2000-0000
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Formulation and Device selection: Bridging the Gap Between Preclinical Species and first-in-human Studies

Abstract: The factors that influence inhaled first-in-human (FIH) device and formulation selection often differ significantly from the factors that have influenced the preceding preclinical experiments and inhalation toxicology work. In order to minimize the risk of delivery issues negatively impacting a respiratory pipeline program, the preclinical and FIH delivery systems must be considered holistically. This topic will be covered in more detail in this paper. Several examples will be presented that highlight how appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Thus, a through characterization of the performance of the inhalation device is required at regulatory level, when developing an OID. Such characterization is based on in vitro, ex vivo and in vivo (on human volunteers) tests, as extensively described in the scientific literature [26][27][28][29][30][31][32][33] and in the guidelines published by the European Medicine Agency (EMA) (CPMP/EWP/4151/00; CPMP/EWP/239/95; CPMP/180/95; CPMP/QWP/158/96; CPMP/OWP/2845/00; EMEA/CHMP/QWP/49313/2005; CPMP/EWP/4151/00 and EMEA/CHMP/EWP/48501/2008 Appendix 1). Animal models are not used in the characterization of the efficiency and reproducibility of inhalation delivery devices.…”
Section: Inhalation Therapymentioning
confidence: 99%
“…Thus, a through characterization of the performance of the inhalation device is required at regulatory level, when developing an OID. Such characterization is based on in vitro, ex vivo and in vivo (on human volunteers) tests, as extensively described in the scientific literature [26][27][28][29][30][31][32][33] and in the guidelines published by the European Medicine Agency (EMA) (CPMP/EWP/4151/00; CPMP/EWP/239/95; CPMP/180/95; CPMP/QWP/158/96; CPMP/OWP/2845/00; EMEA/CHMP/QWP/49313/2005; CPMP/EWP/4151/00 and EMEA/CHMP/EWP/48501/2008 Appendix 1). Animal models are not used in the characterization of the efficiency and reproducibility of inhalation delivery devices.…”
Section: Inhalation Therapymentioning
confidence: 99%
“…Notably, animal models differ by important underlying discrepancies with humans, spanning amongst other anatomical and physiological differences between species ( Hogg and Timens, 2009 ) to broad divergences in immunological ( Mestas and Hughes, 2004 ) and genetic ( Seok et al, 2013 ) responses to inflammatory diseases. Not only do these dissimilarities translate to contrasting delivery protocols when considering in vivo animal experiments ( Wylie et al, 2018 ), but the translational impact of in vivo findings remains frequently questioned in characterizing human diseases ( van der Worp et al, 2010 ). Most significantly, the gap between humans and animals constitutes an inevitable barrier to new therapeutic development ( Barnes et al, 2015a ; Prakash et al, 2017 ) and is underscored with as high as 80% failure on drug efficacy in human trials leveraging molecules previously screened in rodent lungs ( Miller and Spence, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, there have been numerous publications evaluating particulate-based vaccines for pulmonary delivery in preclinical animal models [ 12 , 13 , 14 , 15 , 16 ]. Unfortunately, many of the pulmonary drug and vaccine candidates that are successfully evaluated in preclinical studies do not proceed to clinical trials; the failure to translate preclinical studies into humans is despite a plethora of preclinical studies employing the pulmonary route for therapeutics and vaccine delivery [ 15 , 16 , 17 , 18 , 19 ]. This problem was recently discussed by Muttil and colleagues [ 20 ], who suggested that one of the reasons for poor translation of preclinical studies is due to the different mechanisms by which preclinical inhalation devices operate compared to human inhalers.…”
Section: Introductionmentioning
confidence: 99%